1966
DOI: 10.1099/00221287-42-1-43
|View full text |Cite
|
Sign up to set email alerts
|

DNA Homology and Taxonomy of Pseudomonas and Xanthomonas

Abstract: SUMMARYThe relatedness between several nomen species of the PseudomonasXanthomonas group and some other organisms was numerically fixed through D N A homology and D N A base composition. For Pseudomonas the numerically analysed strains proposed by Lysenko as neotypes were used. The mean Yo (G+C) was in the range 60-67.5. 14C-DNA from either Fseudomonasfluorescens or P. putida was hybridized with D N A from 17 different species centres and the D N A homology was in the range 50-100 %.Genetic species differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…According to these authors, the homology indexes between different strains of E. coli and between several species of Shigella, Salmonella, and Alkalescens-Dispar and E. coli were from 100 to 36%, more than 70, 45, and 88%, respectively, measured by the hydroxapatite binding method. De Ley et al (6) also reported high homology indexes in Pseudomonas (100 to 55%), except two strains which showed low homology indexes (5%), and Xanthomonas (100 to 54%) by interspecific DNA-DNA hybridization.…”
Section: Discussionmentioning
confidence: 93%
“…According to these authors, the homology indexes between different strains of E. coli and between several species of Shigella, Salmonella, and Alkalescens-Dispar and E. coli were from 100 to 36%, more than 70, 45, and 88%, respectively, measured by the hydroxapatite binding method. De Ley et al (6) also reported high homology indexes in Pseudomonas (100 to 55%), except two strains which showed low homology indexes (5%), and Xanthomonas (100 to 54%) by interspecific DNA-DNA hybridization.…”
Section: Discussionmentioning
confidence: 93%
“…The technique of DNA-DNA or DNA-RNA hybridization was introduced into prokaryote systematics from the 1960s onwards (Brenner et al, 1967;De Ley et al, 1966;Johnson & Ordal, 1968;McCarthy & Bolton, 1963;Pace & Campbell, 1971;Palleroni et al, 1973 T m is calculated on the basis of the known DNA G+C content of the strains to be hybridized. The temperature at which the hybridization is carried out must be clearly stated.…”
Section: Nucleic Acid Hybridization Methodsmentioning
confidence: 99%
“…The use of nucleic acid homology techniques has proved valuable in determining genetic relatedness among micro-organisms including various bacteria (Weissman, Reich, Somerson & Cole, 1966;De Ley, Park, Tijtgat & van Ermengem, 1966) and mycoplasmas . One of the methods for determining DNA-RNA hybrid formation is the technique described by Gillespie & Spiegelman (1965).…”
Section: Introductionmentioning
confidence: 99%